TEN-WEEK ADHERENCE TO A COMMERCIAL SMARTPHONE APPLICATION INTERVENTION IN A CLINICAL SAMPLE OF OLDER ADULTS. (11th November 2018) - D'Cunha, N; Naumovski, N; Georgousopoulou, E; Hunter, M; Kellett, J; Mellor, D; McKune, A; Isbel, S
Abstract: The rapid surge in the use of technology has revealed potential for smartphone applications to assist with management of chronic disease in aging populations. However, little data exists surrounding the daily use of a smartphone application by a clinical population of older adults. In the present study, 50 individuals (46 female) aged between 50 and 77 years (mean age=63.1 ± 7.67) and living with arthritis, were recruited to use a photoplethysmography-based commercially-available smartphone application (HRV4Training) to measure heart rate variability to assist with disease management. In total, 45 participants had access to compatible smartphones and were instructed on how to use the application within five minutes of waking for ten weeks (70 days). Six participants either withdrew from the study or were excluded due to technological issues. Of the compliant participants (n=39) their average use was 51.5 days (73.6%), with measurements taken at the incorrect time on 3.64 days (5.20%). The median use was 60 days. At the end of the study, 44.0% of participants reported finding the application helpful, and 43.9% as neither helpful or unhelpful in managing their condition. The findings highlight challenges associated with application-based interventions for older adults including smartphone compatibility issues with older models and attrition due to illness or technology issues. Future health based smartphone applications should consider the needs of older adults as users of this technology. The inclusion of features such as reminder messages, alerts or prompts, may promote user engagement and has the potential to improve self-management of health conditions in this population.